(untitled) (Agora for Physical Education and Sport, 2024)
Service Learning promotes solidarity-based student activities by offering a service while acquiring professional skills linked to a subject, in this case, Final Degree Projects. The aim of this study was to identify university lecturers’ perceptions of their own teaching activities. Three focus groups and two in-depth interviews were carried out to self-evaluate what was done. Results show that the planning, the competences acquired by the students and the challenges for the future are relevant. It can be concluded that the teaching reflection and the opinions of agents involved have improved the training approach and the proposals.